Superior Place Learning of C57BL/6 vs. DBA/2 Mice Following Prior Cued Learning in the Water Maze Depends on Prefrontal Cortical Subregions - Cho, Woo-Hyun; Park, Jung-Cheol; Jeon, Won Kyung; Cho, Jeiwon; Han, Jung-Soo (Frontiers in Behavioral Neuroscience, 2019)
The participation of the prefrontal cortex, hippocampus, and dorsal striatum in switching the learning task from cued to place learning were examined in C57BL/6 and DBA/2 mice, by assessing changed levels of phosphorylated CREB (pCREB). Mice of both strains first received cued training in a water maze for 4 days (4 trials per day), and were then assigned to one of four groups, one with no place training, and three with different durations of place training (2, 4, or 8 days). Both strains showed equal performance in cued training. After the switch to place training, C57BL/6 mice with 2 or 4 days of training performed significantly better than DBA/2 mice, but their superiority disappeared during the second half of an 8 days-place training period. The pCREB levels of these mice were measured 30 min after place training and compared with those of mice that received only cued training. Changes in pCREB levels of C57BL/6 mice were greater in the hippocampal CA3, hippocampal dentate gyrus, orbitofrontal and medial prefrontal cortex than those of DBA/2 mice, when mice of both received the switched place training for 2 days. We further investigated the roles of orbitofrontal and medial prefrontal cortex among these brain regions showing strain differences, by destroying each region using selective neurotoxins. C57BL/6 mice with orbitofrontal lesions were slower to acquire the place learning and continued to use the cued search acquired during the cued training phase. These findings indicate that mouse orbitofrontal cortex pCREB is associated with behavioral flexibility such as the ability to switch a learning task.